(+)- and (−)-ganodilactone, a pair of meroterpenoid dimers with pancreatic lipase inhibitory activities from the macromycete Ganoderma leucocontextum. Issue 69 (8th July 2016) - Chen, He-Ping; Zhao, Zhen-Zhu; Zhang, Yu; Bai, Xue; Zhang, Ling; Liu, Ji-Kai
Abstract : (+)- and (−)-ganodilactone (1 ), a pair of novel meroterpenoid dimers possessing a unique 5′ H -spiro[chroman-4, 2′-furan]-2, 5′-dione ring system were discovered from the fruiting bodies of Ganoderma leucocontextum . Abstract : (+)- and (−)-Ganodilactone (1 ), a pair of novel meroterpenoid dimers possessing a unique 5′ H -spiro[chroman-4, 2′-furan]-2, 5′-dione ring system, along with their biogeneticly-related compound, ganomycin I (2 ), were discovered from the fruiting bodies of Ganoderma leucocontextum . The structures and absolute configurations were assigned with the aid of 1D and 2D NMR spectra, HRESIMS analysis and ECD calculations. (±)-, (+)-, and (−)-ganodilactone (1 ) showed pancreatic lipase inhibitory activities and exhibited the IC50 values as 27.3, 4.0, and 2.5 μM, respectively.